Caracterização microestrutural da fase sigma no aço inoxidável superaustenítico ASTM A744 Gr. CN3MN - Silva, Maria do Socorro da (2015)
Stainless steels are mainly characterized by high corrosion resistance in various environments. This characteristic comes from the formation of a cromium oxide film, requiring at least 11%wt Cr. The superaustenitic stainless steel class is derived from austenitic stainless steel by the addition of alloying elements. The work environment temperature can favour precipitate formation that can affect the mechanical and the corrosion resistance properties of these steels. Due Mo, Ni and Cr content precipitation of secondary phases can occur, being the most common: sigma phase () and chi phase (). For the characterization of the microstructure and of sigma phase formation in superaustenitic steels, solution anneal heat treatments were realized: 1170ºC and 1210ºC for 2h. The heat treated samples were characterized by optical and electron microscopy techniques, besides energy-dispersive X-ray spectroscopy (EDS) and electron backscatter diffraction (EBSD). The results were compared with as received state (as-cast) samples. It can be observed the presence of sigma phase in both heat treatments and as-cast states, but with volume fraction variations as a function of the applied heat treatment.